Pengembangan Petunjuk Praktikum Berorientasi Pemecahan Masalah sebagai Sarana Berlatih Keterampilan Proses dan Hasil Belajar Mahasiswa IPA Universitas Wiraraja - Dyah Ayu Fajarianingtyas; Jefri Nur Hidayat (Jurnal Pendidikan Sains Indonesia, 2020)
Presentation of basic Biology courses integrated between theory and practice, in this case the skills of process and learning outcomes determined in their entirety which can be done in classrooms and labs assisted by practical guide. The research objectives (1) to produce a valid practical guide;(2) differences process skills;(3) improved learning outcomes and(4) respon. This research refers to the 4-D model of Thiagarajan, Semmel Semmel (1974).consists of 4 stages: Define, Design, Develope, and Disseminate. The research subjects used Basic students in the 2019-2020 academic year. At Wiraraja University. Instrument: (1) validation sheets, (2) observation sheets, (3) test sheets. and (4) respons. Data analysis techniques (1) validation data compiled from the score sheet given to expert validators and then averaged on each aspect and used as a percentage form; (2) process skill data using Wilcoxon test; (3) learning outcomes analyzed by N-gain score; and (4) responses analyzed from the average of each indicator and a percentage. Results (1) practical guide valid at 94% (good category); (2) there differences in process skills a significance value of 0,000; (3) there was an increase in learning outcomes show N-gain 0.74 (high criteria); and (4) respons 83% (good criteria)